Iminosugar-Based Nicotinamide Phosphoribosyltransferase (NAMPT) Inhibitors as Potential Anti-Pancreatic Cancer Agents - Irene Conforti; Andrea Benzi; Irene Caffa; Santina Bruzzone; Alessio Nencioni; Alberto Marra (MDPI AG, 2023)
The nicotinamide phosphoribosyltransferase (NAMPT) is considered a very promising therapeutic target because it is overexpressed in pancreatic cancer. Although many inhibitors have been prepared and tested, clinical trials have shown that NAMPT inhibition may result in severe haematological toxicity. Therefore, the development of conceptually new inhibitors is an important and challenging task. We synthesized ten β-d-iminoribofuranosides bearing various heterocycle-based chains carbon-linked to the anomeric position starting from non-carbohydrate derivatives. They were then submitted to NAMPT inhibition assays, as well as to pancreatic tumor cells viability and intracellular NAD+ depletion evaluation. The biological activity of the compounds was compared to that of the corresponding analogues lacking the carbohydrate unit to assess, for the first time, the contribution of the iminosugar moiety to the properties of these potential antitumor agents.